Film tourism as a tool of tourism development: The Representation of Scotland in the Outlander TV series - Potočnik-Topler Jasna; Špenko Tjaša (University Educons, Faculty of Sports and Tourism, Novi Sad, 2019)
This article examines the phenomenon of the latest niche trend that has emerged in the Tourism industry and represents a great part of one destination's economy. It runs under several names, such as Film-induced Tourism, Screen Tourism, Set-Jetting, or, most simply, Film Tourism. The currently trendy story of Outlander, written by Diana Gabaldon and first published in 1990, was examined and analysed in the article. Through what is presently eight thick volumes, we follow the story of two main protagonists, the rebellious but honest Scottish warrior James Fraser, and a 20th century independent but devoted Englishwoman, Claire Randall. The title of the very first book is Outlander, meaning a person who does not come from that particular area and is, in fact, an outsider. Back in the 18th century, to where the mentioned book dates, it also meant an Englishman. The following paper focuses on the important impact of the Outlander series, also named 'Outlander effect', on the perception of Scotland and its heritage around the globe, as well as on Scottish tourist visitation since the TV adaptation of the eponymous name aired in 2014.